Reversible tuning of magnetocaloric Ni-Mn-Ga-Co films on ferroelectric PMN-PT substrates - Schleicher, Benjamin; Niemann, Robert; Schwabe, Stefan; Huehne, Ruben; Schultz, Ludwig; Nielsch, Kornelius; Faehler, Sebastian (Scientific Reports, 2017)
Tuning functional properties of thin caloric films by mechanical stress is currently of high interest. In particular, a controllable magnetisation or transition temperature is desired for improved usability in magnetocaloric devices. Here, we present results of epitaxial magnetocaloric Ni-Mn-Ga-Co thin films on ferroelectric Pb(Mg1/3Nb2/3)0.72Ti0.28O3 (PMN-PT) substrates. Utilizing X-ray diffraction measurements, we demonstrate that the strain induced in the substrate by application of an electric field can be transferred to the thin film, resulting in a change of the lattice parameters. We examined the consequences of this strain on the magnetic properties of the thin film by temperature- and electric field-dependent measurements. We did not observe a change of martensitic transformation temperature but a reversible change of magnetisation within the austenitic state, which we attribute to the intrinsic magnetic instability of this metamagnetic Heusler alloy. We demonstrate an electric field-controlled entropy change of about 31 % of the magnetocaloric effect - without any hysteresis.
CRIS-Team Scopus Importer:2022-04-14